2012
DOI: 10.1155/2012/976425
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Clinimetric Properties of Habitual Physical Activity Measures in Young Children with a Motor Disability

Abstract: Aim. To identify and systematically review the clinimetric properties of habitual physical activity (HPA) measures in young children with a motor disability. Method. Five databases were searched for measures of HPA including: children aged <6.0 years with a neuromuscular disorder, physical activity defined as “bodily movement produced by skeletal muscles causing caloric expenditure”, reported HPA as duration, frequency, intensity, mode or energy expenditure, and evaluated clinimetric properties. The quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Validation studies were most reported in Cerebral Palsy (CP) for paediatrics and Multiple Sclerosis (MS) for adults and only McDonald et al’s StepWatch validation study in DMD [37] was identified as an NMD-population paper; reported by Oftedal et al [35]. …”
Section: Resultsmentioning
confidence: 99%
“…Validation studies were most reported in Cerebral Palsy (CP) for paediatrics and Multiple Sclerosis (MS) for adults and only McDonald et al’s StepWatch validation study in DMD [37] was identified as an NMD-population paper; reported by Oftedal et al [35]. …”
Section: Resultsmentioning
confidence: 99%
“…At stride rate > 60 strides/min hrr was still lower than 55%, whereas < 60% hrr is still considered moderate exercise intensity according to aCSM guidelines (17). an explanation for the relatively low HRR at the highest detected stride rates could be that, as the Stepwatch was calibrated for walking it measured running less accurately, as was noticed during calibration, and this conclusion supported by the low number of children in all groups achieving this stride rate (30). Furthermore, while the Stepwatch averages over 1 min intervals, short bursts of running might be shorter.…”
Section: Intensity Of Stride Rate Activity Levelsmentioning
confidence: 92%
“…9 25 In addition, poor nutrition and growth may have a secondary impact on body composition, bone health and brain maturation, as well as participation and health-related quality of life (HRQoL) in later childhood. In our overlapping CP-child study of growth, nutrition and physical activity (NHMRC 569605), 26 we have determined at preschool-age the i) energy requirements, body composition, dietary intake, 27–29 ii) validation of HPA cut-points, 30 iii) validation of a modified 3-day weighed food record for the assessment of energy intake 29 and iv) OPD across the spectrum of functional severity. 31 32 …”
Section: Introductionmentioning
confidence: 99%